Southernmost occurrence of Deltamys kempi (Rodentia, Cricetidae) in Argentina: paleontological and neontological evidence to assess its current distribution - Pardiñas, Ulises Francisco J. (2021)
We report the southernmost locality for the sigmodontine rodent Deltamys kempi Thomas, 1917, in Arroyo Las Tijeras (36°22’43” S, 56°50’12” W, General Lavalle county) near the coast of Buenos Aires province (Argentina), extending the range of the species ca. 150 km S. This record is a wake-up call about the presence of Brazilian fauna well beyond their southernmost suspected limit. Several lines of evidence point to considering D. kempi as a very recent immigrant in Argentina.